2007
DOI: 10.1016/j.biomaterials.2007.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial-mediated retroviral gene transfer using self-assembled monolayers

Abstract: Biomaterial-mediated gene delivery has recently emerged as a promising alternative to conventional gene transfer technologies that focus on direct delivery of viral vectors or DNA-polymer/matrix complexes. However, biomaterial-based strategies have primarily targeted transient gene expression vehicles, including plasmid DNA and adenovirus particles. This study expands on this work by characterizing biomaterial properties conducive to the surface immobilization of retroviral particles and subsequent transductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Our findings extend previous work showing biomaterialmediated gene delivery using viral vectors (20,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The majority of this work demonstrated the ability to specify the spatial location of delivered vectors, rather than the induction of tissuespecific differentiation.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our findings extend previous work showing biomaterialmediated gene delivery using viral vectors (20,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The majority of this work demonstrated the ability to specify the spatial location of delivered vectors, rather than the induction of tissuespecific differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, we showed that material-mediated transduction of hMSCs remained >90% after rinsing the substrates upon which lentivirus was immobilized. Moreover, we have also shown that incubation of PLL-coated surfaces with retrovirus for 16 h results in high levels of transduction of fibroblasts (∼70%) (20), suggesting that the half-life of the vector does not preclude efficient transduction. Collectively, these results support the potential of viral transduction in the joint environment.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations